In vivo imaging of transgenic Brugia malayi. - Canhui Liu; Sai Lata De; Kristi Miley; Thomas R Unnasch (Public Library of Science (PLoS), 2020)
Background Studies of the human filarial parasite have been hampered by the fact that they are obligate parasites with long life cycles. In other pathogenic infections, in vivo imaging systems (IVIS) have proven extremely useful in studying pathogenesis, tissue tropism and in vivo drug efficacy. IVIS requires the use of transgenic parasites expressing a florescent reporter. Developing a method to produce transgenic filarial parasites expressing a florescent reporter would permit IVIS to be applied to the study of tissue tropism and provide a non-invasive way to screen for in vivo drug efficacy against these parasites. Methodology/principal findings We report the development of a dual luciferase reporter construct in a piggyBac backbone that may be used to stably transfect Brugia malayi, a causative agent of human filariasis. Parasites transfected with this construct were visible in IVIS images obtained from infected gerbils. The signal in these infected animals increased dramatically when the transgenic parasites matured to the adult stage and began to produce transgenic progeny microfilaria. We demonstrate that the IVIS system can be used to develop an effective method for cryopreservation of transgenic parasites, to non-invasively monitor the effect of treatment with anti-filarial drugs, and to rapidly identify transgenic F1 microfilariae. Conclusions To our knowledge, this represents the first application of IVIS to the study of a human filarial parasite. This method should prove useful in studies of tissue tropism and as an efficient in vivo assay for candidate anti-filarial drugs.